Scientific production on digital competences in higher education according to Scopus from 2013 to 2023 - Quindemil Torrijo, Eneida María (2024)
In the current era, digital competencies are fundamental in higher education as they not only prepare students and faculty to efficiently use tools, platforms, and technological resources but also develop critical skills such as problem-solving, critical thinking, and autonomous learning. This is important not only for the employability of graduates but also for maintaining the relevance and competitiveness of educational institutions in a global market. The present research aimed to analyze the behavior of Ibero-American scientific production on digital competencies in higher education according to Scopus in the period 2013-2023. A descriptive study with a quantitative, longitudinal, and retrospective approach was conducted. Based on bibliometric indicators, it was possible to provide relevant quantifiable information on specific topics of digital competencies, including the number of publications related to the mentioned theme and the most cited works in the last five years. As a result, it was evidenced that although there is currently a considerable amount of research directly related to digital competencies, it is necessary to address their link with emerging areas such as artificial intelligence, which can have significant consequences in terms of the development of future studies to expand the field of knowledge regarding the scientific discipline.